Update on the management of orbitozygomatic fractures - Mabika Bredel Djeri Djor; Garango Allaye; Lahmiti Saad; Nguessan Dominique; Coulibaly Toua Antoine; Traoré Ibrahïma; Mansouri-Hattab Nadia (EDP Sciences, 2021)
Orbitozygomatic fractures are an important aspect of facial trauma. Although the literature in maxillofacial surgery is rich on the question, this article resulting from the experience of a maxillofacial surgeon brings additional data in the knowledge of the subject. This is particularly the case with regard to the principles of examination, the pathways first, the principles of restraint and osteosynthesis, and the various surgery-related complications, as well as the precautions to be adopted to minimize them. The most important thing to remember is that the management approach is often variable, and the right choice is summed up in the clinical perception and level of expertise and comfort of the surgeon, while also considering the patient's point of view.